2010
DOI: 10.1016/j.jneuroim.2010.02.009
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α, IL-1β, IL-6, and cinc-1 levels in rat brain after meningitis induced by Streptococcus pneumoniae

Abstract: Bacterial meningitis caused by Streptococcus pneumoniae is associated with a significant mortality rate and persisting neurologic sequelae, including sensory-motor deficits, seizures, and impairment of learning and memory. The presence of proliferating bacteria within the subarachnoid and ventricular space compartments triggers an intense inflammatory host response at killing the invading microorganism. Proinflammatory mediators released in the process, including tumor necrosis factor alpha (TNF-alpha), interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 32 publications
4
44
0
Order By: Relevance
“…In a further study, TNFa level in hippocampus, frontal cortex, and CSF were increased, confirming the deleterious effect of TNFa on the brain tissue [30]. It has been also observed that infecting microglia-mixed cultures with L. monocytogenes, increased the MCP-1 and TNF-a levels and reduced levels of IFN-a/b concomitant with a bad prognosis of listeriosis and neuronal destruction by apoptosis [10].…”
Section: Discussionmentioning
confidence: 61%
“…In a further study, TNFa level in hippocampus, frontal cortex, and CSF were increased, confirming the deleterious effect of TNFa on the brain tissue [30]. It has been also observed that infecting microglia-mixed cultures with L. monocytogenes, increased the MCP-1 and TNF-a levels and reduced levels of IFN-a/b concomitant with a bad prognosis of listeriosis and neuronal destruction by apoptosis [10].…”
Section: Discussionmentioning
confidence: 61%
“…In patients suffering from bacterial meningitis, cerebrospinal fluid levels of caspase-1 were increased (258). In children with bacterial meningitis, as well as a rat model of pneumococcal meningitis, increased IL-1␤ levels were measured in the CSF (30,86). Koedel et al showed that mice lacking caspase-1 displayed less severe inflammation and improved survival in a pneumococcal meningitis mouse model (258).…”
Section: Pattern Recognition Receptorsmentioning
confidence: 99%
“…GRO-␣ was also found at high levels in the CSF of patients with bacterial meningitis (553), as well as in a rat model of pneumococcal meningitis, but it did not exert any chemotactic activity (30,553 …”
Section: Chemokinesmentioning
confidence: 99%
“…TNF-α leads to NF-κB activation in the CSF and brain resident cells, which regulates the expression of many pro-inflammatory mediators 29 . In animal models for pneumococcal meningitis, TNF-α was produced in the first 6 h of the immune response 30 . Intrathecal administration of TNF-α results in a similar pathophysiological characteristic of bacterial meningitis such as BBB disruption, facilitating bacterial traversal into the CSF 31 , on the other hand, TNF-α deficient mice increased mortality and spatial memory deficits 32 .…”
Section: Inflammation Cytokinesmentioning
confidence: 99%
“…IL-1β has potent stimulatory effects on granulocytes white cells; it promotes the adhesion of neutrophils and monocytes in endothelial cells 33 . IL-1β is found in the CSF of patients with bacterial meningitis 34 , furthermore, in animal models it was produced in the first 24 h after pneumococcal meningitis induction 30 , although intrathecal administration of IL-1β did not lead to CSF pleocytosis or brain edema 35 . However, the mortality was significantly higher and earlier in the course of the disease among IL-1 receptor (IL-1R) gene-deficient mice, demonstrating that endogenous IL-1β is required for an adequate host defense in pneumococcal meningitis 36 .…”
Section: Inflammation Cytokinesmentioning
confidence: 99%